Does Demutualization Spur Liquidity? - Farman Ali; Man Wang; Imran Ali; Syed Tauseef ALi (SEISENSE Journal of Management, 2020)
Purpose: The literature on demutualization is confined to efficiency and social welfare issues. Little empirical literature exists on the effect of demutualization on listed firms. This study examines the impact of demutualization on the liquidity of listed firms’ stocks. Methodology: It empirically investigates how the liquidity of listed firms’ stocks is affected by demutualization. Analyzing data of 137 non-financial firms listed on the Pakistan Stock Exchange for 2005 to 2017, we employ fixed effect regression to test the hypotheses. Findings: We find that demutualization has significantly improved liquidity. We analyze all three dimensions of liquidity that are the trading activity, market impact, and transaction cost. We find that demutualization increases trading activity, improve market depth, and has reduced the transaction cost. Implications: Our findings suggest that demutualization is beneficial not only for listed firms but also for its shareholders as all three dimensions of liquidity are improved by demutualization. Stock exchanges that are not demutualized and are facing liquidity problem, can be improved by changing its structure from mutual to demutualized. Originality: Prior literature focuses on the impact of demutualization on the stock market or social welfare. There is scares research on the effect of demutualization of the listed firm. This study fills this gap by analyzing the impact of demutualization on listed firms' liquidity in a developing economy, such as Pakistan.